Identification of functional single nucleotide polymorphism of Populus trichocarpa PtrEPSP‐TF and determination of its transcriptional effect. (3rd January 2020) - Xie, Meng; Zhang, Jin; Singan, Vasanth R.; McGranahan, Melissa J.; LaFayette, Peter R.; Jawdy, Sara S.; Engle, Nancy; Doeppke, Crissa; Tschaplinski, Timothy J.; Davis, Mark F.; Lindquist, Erika; Barry, Kerrie; et al.
Abstract: In plants, the phenylpropanoid pathway is responsible for the synthesis of a diverse array of secondary metabolites that include lignin monomers, flavonoids, and coumarins, many of which are essential for plant structure, biomass recalcitrance, stress defense, and nutritional quality. Our previous studies have demonstrated that Populus trichocarpa PtrEPSP‐TF, an isoform of 5‐enolpyruvylshikimate 3‐phosphate (EPSP) synthase, has transcriptional activity and regulates phenylpropanoid biosynthesis in Populus . In this study, we report the identification of single nucleotide polymorphism (SNP) of PtrEPSP‐TF that defines its functionality. Populus natural variants carrying this SNP were shown to have reduced lignin content. Here, we demonstrated that the SNP‐induced substitution of 142nd amino acid (PtrEPSP‐TF D142E ) dramatically impairs the DNA‐binding and transcriptional activity of PtrEPSP‐TF. When introduced to a monocot species rice ( Oryza sativa ) in which an EPSP synthase isoform with the DNA‐binding helix‐turn‐helix (HTH) motif is absent, the PtrEPSP‐TF, but not PtrEPSP‐TF D142E, activated genes in the phenylpropanoid pathway. More importantly, heterologous expression of PtrEPSP‐TF uncovered five new transcriptional regulators of phenylpropanoid biosynthesis in rice. Collectively, this study identifies the key amino acid required for PtrEPSP‐TF functionality and provides a strategy to uncover new transcriptional regulators in phenylpropanoid biosynthesis.